Halal or not? Exploring Muslim perceptions of cultured meat in Singapore - Ho, Shirley S.; Ou, Mengxue; Vijayan, Andrew Vimal (Frontiers in Sustainable Food Systems, 2023)
Singapore was the first country to approve cultured meat for public consumption. However, it remains unclear whether Muslims, who adhere to religious dietary restrictions and constitute a significant proportion of Singapore’s population, are willing to consume cultured meat. Informed by the cognitive miser model, this study explores how Muslims make sense of cultured meat through their religious beliefs, trust in different stakeholders, as well as their risk or benefit perceptions of cultured meat. The findings from online focus group discussions showed that Muslim participants would only consider consuming cultured meat if it is certified halal (i.e., compliant with Islamic laws) and they demonstrated religious concerns about cultured meat. Muslims have strong trust in food regulatory authorities in providing information about the safety and halal status of cultured meat. In addition to religious concerns, Muslims had similar risk and benefit perceptions of cultured meat to non-Muslims. Theoretical and practical implications were discussed.